Argulus coregoni (Crustacea: Branchiura: Argulidae) Parasitic on a Freshwater Minnow Opsariichthys platypus (Cypriniformes: Xenocyprididae) in a Low-Elevation Stream in Kyushu, Western Japan - Kazuya Nagasawa; Naoki Miyajima (Species Diversity, 2025)
An adult female of Argulus coregoni Thorell, 1864 was collected from the operculum of a freshwater minnow Opsariichthys platypus (Temminck and Schlegel, 1846) (Cypriniformes: Xenocyprididae) at 15 m elevation in a stream in Oita Prefecture, Kyushu, western Japan. This adult female of A. coregoni is described herein, and freshwater minnow represents a new host record for this parasite. In central Japan, A. coregoni is known to infect salmonids and a plecoglossid Plecoglossus altivelis altivelis (Temminck and Schlegel, 1846) (both Salmoniformes) in the upper and middle-lower reaches of rivers, respectively, and to use cypriniform fishes as its hosts in low-elevation streams. In contrast, almost nothing is known about the host utilization and distribution of A. coregoni in Kyushu, where the species was collected only once from a land-locked salmonid fish at a high elevation in a mountain stream. The present collection of A. coregoni from freshwater minnow suggests that this parasite infects cypriniform fishes in low-elevation streams in Kyushu as well. Based on new information on the leg morphology of the specimen of A. coregoni collected in this study, an amended key is provided for the five species of the genus found on Japanese freshwater fishes.